ANALISIS MENGENAI HAK ANAK YANG MENJADI PELAKU KEKERASAN SEKSUAL: PENERAPAN DIVERSI PERWUJUDAN DARI RESTORATIVE JUSTICE - Wibisono, Eko; Ahmad, Masduki; Sanusi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the increasing incidence of sexual violence against children in Indonesia, including cases in which the perpetrators are also children, thereby creating a legal dilemma between the protection of child offenders through diversion and restorative justice on the one hand, and the fulfillment of victims’ rights on the other. The objective of this research is to analyze the implementation of restorative justice within the juvenile criminal justice system and to examine the balance of legal protection between child offenders and victims based on the Juvenile Criminal Justice System Law (UU SPPA) and the Sexual Violence Crime Law (UU TPKS). The study employs a normative legal research method with statutory, conceptual, and case approaches, using library research analyzed through descriptive qualitative techniques. The findings indicate that the implementation of diversion and restorative justice in cases of sexual violence committed by children remains inconsistent and tends to be applied selectively. Its implementation faces several obstacles, including differences in interpretation among law enforcement officials, limited resources, public resistance, and inadequate rehabilitation facilities. In addition, the fulfillment of victims’ rights is still suboptimal due to the risk of re-victimization and limited recovery services. This study concludes that regulatory harmonization is necessary, along with a more selective application of restorative justice based on psychological assessments, in order to achieve a balanced legal protection for both child offenders and victims. Keywords: Restorative Justice, Child Diversion, Child Sexual Violence.